심층 신경망을 활용한 전자문서 내 객체의 자동 추출 방법 연구 - 장희진; Heejin Jang; 채영훈; Yeonghun Chae; 이상원; Sangwon Lee; 조진용; Jinyong Jo (정보처리학회 논문지 (KTSDE), 2018)
인공지능 기술의 확산으로 인해 과학기술 분야에서도 연구 데이터의 확보, 저장 및 활용이 중요시 되고 있는 상황이다. 연구 데이터를 확보하기 위해 전자문서 형태의 연구논문으로부터 그래프, 표와 같은 유의미한 객체를 추출하는 다양한 방법들이 제안되고 있다. 경험적 방법론을 이용하는 기존의 연구들은 문서의 편집 특성을 일반화하여 객체들을 추출하기 때문에 다수의 이질적인 형태를 갖는 전자문서들을 대상으로 연구결과를 적용하는데는 한계가 있다. 본 논문은 경험적 방법론의 경직성을 극복하고 이질적인 전자문서들로부터 목표 객체들을 효과적으로 추출하기 위해 심층 학습 기반의 객체 추출 시스템을 제안한다. 텐서플로우 객체 탐지 API의 Faster R-CNN 알고리즘을 기반으로 새로운 학습모델을 생성했으며 심층 학습과 평가를 위해 총 100여 편의 연구논문들을 대상으로 목표 객체들을 데이터화했다. 마지막으로 성능평가를 통해 제안한 시스템이 경험적 방법론을 적용한 비교 대상에 비해 약 5.2% 높은 성능을 보임을 확인하였다. With the proliferation of artificial intelligence technology, it is becoming important to obtain, store, and utilize scientific data in research and science sectors. A number of methods for extracting meaningful objects such as graphs and tables from research articles have been proposed to eventually obtain scientific data. Existing extraction methods using heuristic approaches are hardly applicable to electronic documents having heterogeneous manuscript formats because they are designed to work properly for some targeted manuscripts. This paper proposes a prototype of an object extraction system which exploits a recent deep-learning technology so as to overcome the inflexibility of the heuristic approaches. We implemented our trained model, based on the Faster R-CNN algorithm, using the Google TensorFlow Object Detection API and also composed an annotated data set from 100 research articles for training and evaluation. Finally, a performance evaluation shows that the proposed system outperforms a comparator adopting heuristic approaches by 5.2%.